Dynamic Culture of Mesenchymal Stromal/Stem Cell Spheroids and Secretion of Paracrine Factors - Fuentes, Paloma; Torres, María José; Arancibia, Rodrigo; Aulestia, Francisco; Vergara, Mauricio; Carrión, Flavio; Osses, Nelson; Altamirano, Claudia (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, conditioned medium (CM) obtained from the culture of mesenchymal stromal/stem cells (MSCs) has been shown to effectively promote tissue repair and modulate the immune response in vitro and in different animal models, with potential for application in regenerative medicine. Using CM offers multiple advantages over the implantation of MSCs themselves: 1) simpler storage, transport, and preservation requirements, 2) avoidance of the inherent risks of cell transplantation, and 3) potential application as a ready-to-go biologic product. For these reasons, a large amount of MSCs research has focused on the characterization of the obtained CM, including soluble trophic factors and vesicles, preconditioning strategies for enhancing paracrine secretion, such as hypoxia, a three-dimensional (3D) environment, and biochemical stimuli, and potential clinical applications. In vitro preconditioning strategies can increase the viability, proliferation, and paracrine properties of MSCs and therefore improve the therapeutic potential of the cells and their derived products. Specifically, dynamic cultivation conditions, such as fluid flow and 3D aggregate culture, substantially impact cellular behaviour. Increased levels of growth factors and cytokines were observed in 3D cultures of MSC grown on orbital or rotatory shaking platforms, in stirred systems, such as spinner flasks or stirred tank reactors, and in microgravity bioreactors. However, only a few studies have established dynamic culture conditions and protocols for 3D aggregate cultivation of MSCs as a scalable and reproducible strategy for CM production. This review summarizes significant advances into the upstream processing, mainly the dynamic generation and cultivation of MSC aggregates, for de CM manufacture and focuses on the standardization of the soluble factor production.